Britain’s Attitude Toward 1980 Moscow Summer Olympics - Al-Dulaimi, Nizar Taher Hussein; Mahmoud Al-Qaisi, Prof. Dr. Mahmoud Abdel Wahed (South Eastern European Journal of Public Health, 2024)
Political, economic, and ideological considerations have been major forces behind the Olympics since their inception. Numerous instances exist, including Hitler's attempts to showcase the might and triumph of the Nazi regime in the 1936 Berlin Olympics, Japan's attempts in 1964 Tokyo Olympics to overcome the legacy of its World War II defeat, and the Republic of Korea's display of the success of its democratic experiment. In the year 1988 in terms of technology. Taking advantage of the US boycott of the 1980 Moscow Games, this study attempts to look into the strategies employed by Britain to stop its athletes from competing in those events. Confusion prevailed among the governments of Carter and Thatcher, as well as among the allied nations and the International Olympic Committee, due to the boycott's unclear objectives.